Characterising Micro-Cracks In Crystalline Silicon Solar Cells Using Transflection Imaging - Teo, Teow Wee (2020)
Existing state-of-the-art methods such as electroluminescence and photoluminescence are commonly used today to detect micro-cracks in solar cells as they are typically invisible to naked human eyes. However, images that these tools produce was found to be difficult to process as they contain many unwanted noises that are in distinguishable to micro-cracks, therefore resulting in low detection accuracy. Other techniques such as the optical transmission method only works at the silicon wafer stage. Moreover, this method was also found to be prone to error due to interference from saw marks caused by recent changes to the wafer sawing technique. Solving this problem has lead to a design of an imaging system based on light transflection principle. In this case, an incident light enters a silicon wafer or a solar cell and is diffusely scattered in multiple directions. As a result, an area in the vicinity of the incident light is illuminated from beneath the surface. The presence of micro-cracks along the transmission path of the transflected light causes an abrupt change in the illumination intensity, thereby creating a shadow representation of the defect. This transmission of light however is not influenced by saw marks, grain boundaries, dislocations, cosmetic scratches, etc. Therefore, micro-cracks in images produced by the proposed method are distinctively visible compared to images acquired by existing methods. On average, the proposed method resulted in classification accuracy of at least 96.7%, which is significantly higher than existing methods. The system was also found to be capable of throughputs of at least 3600 units per hour. Therefore, such a method is ideally suited as an in-line inspection tool in today’s high throughout production environment.